Modifiable Risk Factor of Coronary Heart Disease Incident on Patients with Diabetes Mellitus Type 2 - Masrizal Dt Mangguang; Sri Hardian (Intelektual Pustaka Media Utama, 2016)
The aim of this research is to determine the risk factors related to coronary heart disease incidence in type 2 diabetes mellitus patient at Dr. M. Djamil Padang Hospital. This was an analytic research with case control study design around October 2014 until May 2015. Samples consisted of 39 cases and 39 controls with matching age and sex. The data were analyzed by using univariate, bivariate by using McNemar test, multivariate by using regression logistic test and stratification. The result showed that hypertension p=0.002 (OR=5, 95%CI 1.09-22.82), obesity p= 0.0001 (OR=6, 95%CI 2.08-17.29), duration of DM p= 0.01 (OR=3.2, 95% CI 1.17-8.73) and smooking p= 0.002 (OR=7, 95%CI 1.59-30.80) were associated with coronary heart disease incidence in type 2 DM patient. The most dominant risk factor that was associated with coronary heart disease incidence in type 2 DM patient at Dr. M. Djamil Hospital was obesity p= 0.0001 (OR=10.2, 95% CI 3.08-33.81). Hypertension OR=11.25, duration of DM OR=18, smooking OR=16.2, sport activity OR=18.6 and income level OR=15.7 had interaction of the association between obesity and coronary heart disease incidence in type 2 DM patient. Hypertension, obesity, duration of DM and smooking were risk factors that associated to coronary heart disease incidence in type 2 DM patient. Then, the most dominant risk factor that associated to coronary heart disease incidence in type 2 DM patient at Dr. M. Djamil Padang was obesity. Hypertension, duration of DM, smooking, sporct activity and income level had interaction of the association between obesity and coronary heart disease incidence in type 2 DM patient.